Optical Sensing and Detection 2010
DOI: 10.1117/12.854476
|View full text |Cite
|
Sign up to set email alerts
|

A low cost mid-infrared sensor for on line contamination monitoring of lubricating oils in marine engines

Abstract: The chemical and physical condition of oils in marine engines must be monitored to ensure optimum performance of the engine and to avoid damage by degraded oil not adequately lubricating the engine. Routine monitoring requires expensive laboratory testing and highly skilled analysts. This work describes the adaptation and implementation of a mid infrared (MIR) sensor module for continued oil condition monitoring in two-stroke and four-stroke diesel engines. The developed sensor module will help to reduce costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Through the use of multivariate PLS regression for the sensor calibration, the information content of all infrared channels is used to determine oxidation, water content, and AN of the oil. The optical bandpass filters for NDIR condition monitoring of phosphate-ester hydraulic fluid [ 12 , 13 ], gas engine oil [ 14 ] and diesel engine oil [ 15 ] were selected on the basis of previous knowledge of the chemical reactions occurring during the oil aging process. We have shown that the bandpass filters can also be selected by means of a regression analysis, which means that no prior knowledge of the chemical aging behavior of the oil is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the use of multivariate PLS regression for the sensor calibration, the information content of all infrared channels is used to determine oxidation, water content, and AN of the oil. The optical bandpass filters for NDIR condition monitoring of phosphate-ester hydraulic fluid [ 12 , 13 ], gas engine oil [ 14 ] and diesel engine oil [ 15 ] were selected on the basis of previous knowledge of the chemical reactions occurring during the oil aging process. We have shown that the bandpass filters can also be selected by means of a regression analysis, which means that no prior knowledge of the chemical aging behavior of the oil is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As infrared spectrometers are relatively expensive and are usually not robust enough to be operated in industrial environments, approaches that use non-dispersive infrared (NDIR) measurement setups have been made to monitor additive depletion [ 10 ] or oil oxidation [ 11 ]. NDIR setups for monitoring phosphate-ester hydraulic fluid [ 12 , 13 ], gas engine oil [ 14 ], and diesel engine oil [ 15 ] have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…The Posseidon project (Progressive Oil Sensor System for Extended Identification ON-Line) addressed this by using sophisticated sensors to monitor the condition of lubricating oil. This provides not only a snapshot of the performance of the oil but also provides indications of other engine faults which result in contamination of the oil (Baglee and Knowles 2010a,b, Gorritaxetegi et al 2007, Mohammadi et al 2010. The sensors developed are capable of making measurements of oil properties including:…”
Section: Tools For Gathering Datamentioning
confidence: 99%
“…The accelerated oxidation, fires and contamination of the lubrication oil could be detected by the OCM. Mohammadi et al 14 have designed a novel on-line mid-infrared sensor with low cost for oil monitoring of marine engines. Villar et al 15 designed a visible-near infrared (400–1100 nm) sensor to monitor the characteristics of in-use marine engine oil.…”
Section: Introductionmentioning
confidence: 99%